A Task-Oriented Software Maintenance Model - Abdur Rashid, Mohammad; W. N. Lo, Bruce (Malaysian Journal of Computer Science, 2017)
Software maintenance is the only phase in the system life cycle that does not have any firm theoretical foundation for its practice due to the lack of precise definitions and a maintenance model defining the tasks involved. This paper presents a generic software maintenance model based on various tasks. It also focuses on the relationship between software development and the software maintenance process in terms of software lifecycle model. This model of software maintenance illustrates a comprehensive approach attempting to integrate the software maintenance process with that of software development in a single software life cycle framework.